Highly efficient and stable perovskite solar cells based on di-ammonium ion doping

CN116390509BActive Publication Date: 2026-10-30HEBEI UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310020279.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-05
Publication Date
2026-10-30
Estimated Expiration
2043-01-05

AI Technical Summary

Technical Problem

[0004]本发明针对钙钛矿太阳能电池在空气中放置长时稳定性差和钙钛矿层分解不能商业化应用问题,提供一种基于二铵离子掺杂的高效稳定钙钛矿太阳能电池

Benefits of technology

[0028]本发明提供的一种基于二铵卤化盐掺杂的高效稳定钙钛矿太阳能电池得到显著改善,在空气中放置720h后依然保持有原始光电转换效率的80%;而没有加入添加剂的钙钛矿太阳能电池在放置500h后保持原始光转换效率的80%。因此,本发明得到钙钛矿太阳能电池稳定性得到显著改善,相比于没有添加的钙钛矿太阳能电池,可增加太阳能转换功效,延长太阳能电池使用寿命,降低生产成本,便于应用于大规模光伏发电领域。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116390509B_ABST
    Figure CN116390509B_ABST
Patent Text Reader

Abstract

The application discloses a kind of high-efficiency stable perovskite solar cells based on two ammonium ion doping.The solar cell is sequentially from bottom to top ITO conductive glass, electron transport layer, perovskite absorption layer doped with two ammonium halide salt, hole transport layer and gold electrode;The chemical formula of the perovskite layer is Rb 0.02‑0.05 (FA 0.75‑ 0.95 Cs 0.05‑0.25 ) 0.98‑0.95 PbI 2.91 Br 0.03 Cl 0.06 ;Thickness is 300-500nm;The doping amount of two ammonium salt in perovskite absorption layer is 0.1-2mol% of the molar mass of lead iodide in perovskite.The perovskite solar cell of the application increases the efficiency and stability of perovskite solar cell while maintaining the original perovskite crystal structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention provides a high-efficiency and stable perovskite solar cell based on diammonium ion doping, which belongs to the field of novel photovoltaic solar cells. Background Technology

[0002] Significant progress has been made in the development of perovskite solar cells over the past 20 years. To date, the certified world record power conversion efficiency for perovskite solar cells has reached 25.5%, while organic-inorganic hybrid perovskite solar cells have achieved remarkable results and have become the focus of current research. This is due to the inherently superior photoelectric performance of perovskite materials, which possess long carrier diffusion lengths, tunable band gaps, and high absorption coefficients. The best photoelectric performance of PSCs is achieved with a MA / FA mixed cation formulation (methylammonium (MA: CH3NH3)). + Formic acid (FA:HC(NH2)2) + However, stability issues have hindered its widespread commercial application. The primary reason is the decomposition of perovskite in humid, high-temperature, and oxygen-rich environments. But the fundamental reason is the formation of weak chemical bonds in perovskite, such as ionic bonds, hydrogen bonds, and van der Waals interactions, which also induce defects in perovskite, including metaplastic anhydride (MA). + / FA + / Cs + Vacancy, free Pb 2+ Ion and halide vacancies. Analysis shows that effective passivation of defects is crucial for further improving efficiency and stability, especially humidity stability.

[0003] To overcome these shortcomings and improve efficiency while maintaining stability, researchers have explored various methods, such as component engineering, interface engineering, and surface morphology. One of the simplest methods is additive engineering, where additives are added to the precursor solution. Additives in perovskites are categorized into Lewis acids, low-dimensional perovskites, ionic liquids, and ammonium salts. Lewis acids possess the ability to accept a pair of non-bonding electrons, enabling them to passivate electron-rich defects. Adding lead thiocyanate (Pb(SCN)₂) to the perovskite precursor allows for the formation of MA... + Cations and thiocyanates (SCN) - Anions combine to form volatiles, reducing defects induced by free ammonium salts. Adding Lewis bases containing ammonium salts forms hydrogen bonds with halides in perovskite, inhibiting the migration of halide and A-site ions, thereby reducing perovskite defects and improving the efficiency and stability of perovskite solar energy. Long chains of organic macromolecules in low-dimensional perovskites form a two-dimensional layered structure on the perovskite surface, enhancing its hydrophobicity. However, the two-dimensional perovskite structure results in a large band gap, reducing its photoelectric conversion efficiency. Furthermore, the liquid state of ionic liquids themselves leads to high cost and difficulties in storage and transportation, limiting their widespread application. Summary of the Invention

[0004] This invention addresses the problems of poor stability of perovskite solar cells when exposed to air for extended periods and the decomposition of the perovskite layer, which hinders their commercial application. It provides a high-efficiency and stable perovskite solar cell based on diammonium ion doping. This cell uses a halide salt containing diammonium ions as an additive. The diammonium cations in the additive can fill cation defects at grain boundaries through ionic bonding, while the halide ions introduced from the diammonium cations fill halide vacancies. Through this synergistic effect, defects in the perovskite are reduced. This invention increases the efficiency and stability of perovskite solar cells while maintaining the original perovskite crystal structure.

[0005] The technical solution of this invention is as follows:

[0006] A high-efficiency and stable perovskite solar cell based on diammonium ion doping, wherein the solar cell comprises, from bottom to top, ITO conductive glass, an electron transport layer, a perovskite absorber layer doped with diammonium halide, a hole transport layer and a gold electrode;

[0007] The chemical formula of the perovskite layer is Rb 0.02-0.05 (FA 0.75-0.95 Cs 0.05-0.25 ) 0.98- 0.95 PbI 2.91 Br 0.03 Cl 0.06 (Subscripts indicate molar ratios); Thickness is 300-500 nm;

[0008] The doping amount of diammonium halide in the perovskite absorber layer is 0.1-2 mol% of the molar mass of lead iodide in the perovskite;

[0009] The specific diammonium halide salts incorporated are 2,2-dimethyl-1,3-propanediammonium hydroiodate, 1,4-phenylenediammonium hydroiodate, 1,6-hexammonium diiodate, N,N-2-ethylcyclohexane-1,4-diammonium hydrochloride, N,N-2-methyl-1,4-butanediammonium hydrochloride, N,N-dimethyl-p-diammonium hydrochloride, N,N-dimethyl(4-piperidinyl)methylammonium diammonium hydrochloride, (S)-3-(1-aminoethyl)-N,N-dimethylphenylenediammonium hydrochloride, and (R)-N,N-diethylpyrrolidine-3-diammonium hydrochloride. N,N-Dimethyl-1,2-diammonium hydrochloride, N,N,N',N'-Tetramethyl-terephthalic acid diammonium hydrochloride, N,N,N'-Triethylethylenediammonium hydrochloride, N,N-Diphenylethylenediammonium hydrochloride, 2,2'-(ethylenedioxy)bis(ethylenediammonium)hydroiodide, VUF8430 diammonium hydrobromide, 1,4-Phenylacetic dimethylammonium dibromide, 1,4-Phenylacetic dimethyl diiodide, N1-(tert-butyl)ethane-1,2-diammonium hydrochloride, N1-Isopropyl-N2,N2-Dimethylethane-1,2-diammonium hydrochloride.

[0010] The hole transport layer is made of Spiro-OMeTAD material and has a thickness of 200-500nm.

[0011] The electron transport layer is made of SnO2 and has a thickness of 10-30 nm.

[0012] The thickness of the ITO conductive glass substrate is 300-600nm;

[0013] The thickness of the gold electrode is 60-200 nm;

[0014] The method for fabricating a high-efficiency and stable perovskite solar cell based on diammonium ion doping includes the following steps:

[0015] (1) Fabrication of the electron transport layer:

[0016] A tin dioxide solution with a volume ratio of SnO2:water = 1:1-8 is spin-coated onto ozone-treated ITO conductive glass at a rotation speed of 2000-6000 rpm / min to form an electron transport layer of 10-30 nm. The glass is then annealed at 100-180℃ for 20-50 minutes to obtain the electron transport layer.

[0017] (2) Preparation of perovskite light-absorbing layer:

[0018] On the electron transport layer, after spin-coating the perovskite precursor solution, a perovskite absorber layer doped with diammonium halide with a thickness of 300-500 nm is obtained by vacuum flash evaporation.

[0019] The perovskite precursor solution contains 0.1-20 mg / mL diammonium halide, 1.1-1.6 mmol / mL FAI, 0.07-0.37 mmol / mL CsI, 0.025-0.05 mmol / mL RbI, 0.01-0.8 mmol / mL MACl, 0.01-0.1 mmol / mL PbCl2, 1.48-1.70 mmol / mL PbI2, and 0.01-0.15 mmol / mL PbBr2; the solvents are NMP and DMF, with a volume ratio of NMP:DMF = 1:4-9.

[0020] The spin coating speed is 2000-6000 rpm / min, the time is 3-20s, the annealing temperature is 100-150℃, and the time is controlled at 3-50min. The structure of the device is ITO / SnO2 / diammonium halide-doped perovskite.

[0021] (3) Preparation of hole transport layer:

[0022] Spiro-OMeTAD hole transport layer solution was spin-coated onto the surface of the perovskite light absorption layer at a spin speed of 3000-4500 rpm and a thickness of 200-500 nm to obtain the hole transport layer.

[0023] (4) Fabrication of gold electrodes:

[0024] The device obtained in step (3) is placed in a thermal evaporator, and the vacuum level is 10. -4 -10 -6 After Pa, Au electrodes with a thickness of 60-200 nm are deposited at an evaporation rate of 0.1-0.9 nm / s, ultimately obtaining a high-efficiency and stable perovskite solar cell based on diammonium ion doping.

[0025] The Spiro-OMeTAD hole transport layer solution provided in step (3) is prepared as follows: 50-150 mg of Spiro-OMeTAD powder is added to a container, followed by 10-40 μL of 4-tert-butylpyridine, 10-50 μL of acetonitrile containing lithium bis(trifluoromethanesulfonyl)ammonium, and finally 1-5 mL of chlorobenzene to obtain the hole transport layer precursor solution.

[0026] The concentration of the acetonitrile solution of lithium bis(trifluoromethanesulfonyl)ammonium is 400–600 mg / mL.

[0027] The beneficial effects of this invention are as follows:

[0028] This invention provides a significantly improved high-efficiency and stable perovskite solar cell based on diammonium halide doping. After being placed in air for 720 hours, it retains 80% of its original photoelectric conversion efficiency; while a perovskite solar cell without additives retains 80% of its original photoelectric conversion efficiency after 500 hours. Therefore, the stability of the perovskite solar cell obtained by this invention is significantly improved. Compared with a perovskite solar cell without additives, it can increase solar energy conversion efficiency, extend the lifespan of the solar cell, reduce production costs, and facilitate its application in large-scale photovoltaic power generation. Attached Figure Description

[0029] Figure 1 This is a structural diagram of the doped diammonium halide perovskite solar cell device of the present invention;

[0030] In the figure, there are ITO conductive glass 1-1, SnO2 electron transport layer 1-2, perovskite light absorption layer doped with diamine halide salt 1-3, Spiro-OMeTAD hole transport layer 1-4, and gold electrode 1-5.

[0031] Figure 2 The image shows a scanning electron microscope (SEM) image of the doped 2,2-dimethyl-1,3-propanediammonium hydroiodate diammonium halide perovskite thin film obtained in Example 1.

[0032] Figure 3 The image shows a scanning electron microscope (SEM) image of the undoped diammonium halide perovskite thin film obtained in Comparative Example 1.

[0033] Figure 4 The JV (current-voltage) test curves of the perovskite solar cell devices obtained in Comparative Example 1 and Example 1 are shown.

[0034] In the figure: JV test curve 4-1 of the undoped diammonium halide perovskite solar cell of Comparative Example 1, and JV test curve 4-2 of the doped 2,2-dimethyl-1,3-propanediammonium hydroiodate diammonium halide perovskite solar cell of Example 1;

[0035] Figure 5 Stability curves of the perovskite solar cell devices obtained in Comparative Example 1 and Example 1;

[0036] Figure 5-1 shows the stability curve of the undoped diammonium halide perovskite solar cell in Comparative Example 1, and Figure 5-2 shows the stability curve of the doped 2,2-dimethyl-1,3-propanediammonium hydroiodate diammonium halide perovskite solar cell in Example 1. Detailed Implementation

[0037] The following description, in conjunction with specific embodiments, illustrates a perovskite solar cell based on diammonium halide doping according to the present invention. The purpose is to enable the public to better understand the technical content, rather than to limit the technical content.

[0038] Example 1

[0039] A novel CsFAPbI3-based perovskite solar cell based on 2,2-dimethyl-1,3-propanediammonium hydroiodate doping:

[0040] (1) Preparation of electron transport layer: Tin dioxide was spin-coated on ozone-treated ITO conductive glass with a volume ratio of SnO2:water = 1:4 and a rotation speed of 4000 rpm / min to form a 20 nm electron transport layer. The layer was then annealed at 130 °C for 20 minutes to obtain an ITO / SnO2 structure.

[0041] (2) Preparation of perovskite light-absorbing layer: A perovskite precursor solution was spin-coated onto a SnO2 electron transport layer, and a perovskite absorber layer with a thickness of 350 nm doped with 2,2-dimethyl-1,3-propanediammonium hydroiodate was prepared by vacuum flash evaporation.

[0042] The perovskite precursor solution was prepared as follows: 2 mg of 2,2-dimethyl-1,3-propanediammonium hydroiodate, 1.4 mmol of FAI, 0.07 mmol of CsI, 0.03 mmol of RbI, and 0.06 mmol of MACl (MA: CH3NH3). + 0.05 mmol of PbCl2, 1.48 mmol of PbI2, and 0.02 mmol of PbBr2 were dissolved in 1 mL of NMP:DMF solvent at a volume ratio of 1:9 to obtain a precursor solution, which was then spin-coated at 4000 rpm for 10 s. The solution was then subjected to vacuum flash evaporation for 30 s, followed by annealing at 150 °C for 20 min on a heating stage. The resulting device structure was an ITO / SnO2 / diammonium halide-doped perovskite; the chemical formula of the perovskite layer was Rb. 0.02 (FA 0.95 Cs 0.05 ) 0.98 PbI 2.91 Br 0.03 Cl 0.06 The doping molar ratio with diammonium halide salt is 0.37 mol%.

[0043] (3) Preparation of hole transport layer: Spiro-OMeTAD hole transport layer solution that has been dissolved and stored for 2 days in advance is spin-coated on the surface of perovskite light absorption layer. The rotation speed is controlled at 3000 rpm and the thickness is controlled at 300 nm. The structure of the device is ITO / SnO2 / diammonium halide-doped perovskite / Spiro-OMeTAD.

[0044] (4) Fabrication of the metal counter electrode: Place the device obtained in step (3) into a thermal evaporator, and the vacuum degree reaches 10. -4 After Pa, a 90 nm thick Au electrode was deposited at an evaporation rate of 1 nm / s. The structure of the device is as follows. Figure 1 The structure shown is ITO / SnO2 / doped diammonium halide perovskite / Spiro-OMeTAD / Au.

[0045] The pre-prepared Spiro-OMeTAD hole transport layer solution in step (3) is prepared as follows: First, weigh 72.3 mg of Spiro-OMeTAD powder and add it to a reagent bottle, then add 29 μL of 4-tert-butylpyridine solvent, and finally add 18 μL of acetonitrile solution containing lithium bis(trifluoromethanesulfonyl)imide, wherein the concentration of the acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide is 520 mg / mL. Finally, add 1 mL of chlorobenzene to the solvent, mix the solution evenly, and obtain the hole transport layer precursor solution.

[0046] Comparative Example 1

[0047] A CsFAPbI3-based perovskite solar cell

[0048] (1) Preparation of electron transport layer: Tin dioxide was spin-coated on ITO substrate with a volume ratio of SnO2:water = 1:4 and a rotation speed of 4500 rpm to form a 20 nm electron transport layer, and then annealed at 150 °C for 30 minutes to obtain an ITO / SnO2 structure.

[0049] (2) Preparation of perovskite light-absorbing layer: A 500 nm thick CsFAPbI3-based perovskite absorber layer was prepared on an ITO / SnO2 substrate using a low-pressure vacuum flash evaporation method. The perovskite solution concentration was controlled at 1.5 mol / L. Its morphology is as follows: Figure 3 As shown, when the vacuum degree is 10 Pa, the pressure is held for 30 s; it is then annealed on a heating stage at a temperature controlled at 150 °C for 30 min. The structure of the device is ITO / SnO2 / CsFAPbI3-based perovskite.

[0050] (3) Preparation of hole transport layer: The Spiro-OMeTAD hole transport layer solution prepared 12 hours in advance was spin-coated onto the perovskite layer. The rotation speed was controlled at 3500 rpm and the thickness was controlled at 300 nm. The structure of the device is ITO / SnO2 / CsFAPbI3-based perovskite / Spiro-OMeTAD.

[0051] (4) Fabrication of the metal counter electrode: The device is placed in a thermal evaporation process, and the vacuum degree reaches 10. -5 After Pa, an 85 nm thick Au electrode was deposited at an evaporation rate of 0.8 nm / s; the device structure is ITO / SnO2 / undoped diammonium salt perovskite / Spiro-OMeTAD / Au.

[0052] For diammonium-doped 2,2-dimethyl-1,3-propanediammonium hydroiodate perovskite films, such as Figure 2 The image shows a perovskite film without doping, as shown in the image. Figure 3 Analysis revealed that the film doped with 2,2-dimethyl-1,3-propanediammonium hydroiodate perovskite has a smaller grain size and fewer pores, which helps to reduce defects in the perovskite film and improve the efficiency and stability of perovskite solar cells.

[0053] The photoelectric performance of the fabricated solar cell device was tested (according to the ISOS-V-1 test conditions in the Consensus statement forstability assessment and reporting for perovskite photovoltaics based on ISOS procedures), such as... Figure 4 As shown, the open-circuit voltage of the 2,2-dimethyl-1,3-propanediammonium hydroiodate perovskite solar cell device, characterized by current-voltage curves, is 1.12V, and the short-circuit current is 25.59mA / cm. 2 The fill factor is 76.21%, and the photoelectric conversion efficiency is 21.64%. The undoped 2,2-dimethyl-1,3-propanediammonium hydroiodate perovskite solar cell device has an open-circuit voltage of 1.10V and a short-circuit current of 25.21mA / cm². 2The fill factor is 69.18%, and the photoelectric conversion efficiency is 19.23%. As can be seen, the photoelectric conversion efficiency of the 2,2-dimethyl-1,3-propanediammonium hydroiodate perovskite solar cell is significantly higher than that of the undoped 2,2-dimethyl-1,3-propanediammonium hydroiodate perovskite solar cell. The stability time of the 2,2-dimethyl-1,3-propanediammonium hydroiodate perovskite solar cell is longer than that of the undoped 2,2-dimethyl-1,3-propanediammonium hydroiodate perovskite solar cell. The 2,2-dimethyl-1,3-propanediammonium hydroiodate perovskite solar cell retains 80% of its initial efficiency after being placed in air for 720 hours, while the undoped perovskite retains 80% of its initial efficiency after 500 hours. Figure 5 As shown, both efficiency and stability are improved compared to undoped 2,2-dimethyl-1,3-propanediammonium hydroiodate perovskite solar cell devices.

[0054] Example 2

[0055] The other steps are the same as in Example 1, except that 2,2-dimethyl-1,3-propanediammonium hydroiodate is replaced with 1,4-phenylenediammonium hydroiodate. The perovskite solar cell doped with 1,4-phenylenediammonium hydroiodate achieved an efficiency of over 21.58%, which is higher than the efficiency of 19.23% of the perovskite solar cell without diammonium ion doping. This may be because the introduction of macromolecules containing benzene rings, which are regularly distributed in the perovskite, facilitates the transfer of internal electrons. At the same time, the introduction of iodine ions reduces halide ion vacancies, and the stability is improved compared to the device without diammonium ion doping.

[0056] Example 3

[0057] The other steps are the same as in Example 1, except that 2,2-dimethyl-1,3-propanediammonium hydroiodate is replaced with 2,2′-(ethylenedioxy)diethylamine hydroiodate. The stability of the perovskite is improved compared to the undoped diammonium salt perovskite, which may be due to the interaction between the lone pair electrons in oxygen and the lead ions in the perovskite.

[0058] Example 4

[0059] The other steps are the same as in Example 1, except that 2,2-dimethyl-1,3-propanediammonium hydroiodate is replaced with 1,6-hexammonium hydroiodate. The stability of the perovskite is improved compared to the undoped diammonium salt. This may be because the introduction of long-chain diammonium ions forms a two-dimensional perovskite on the perovskite surface, which improves the hydrophobicity of the perovskite film surface and thus improves the stability.

[0060] Example 5

[0061] The other steps are the same as in Example 1, except that 2,2-dimethyl-1,3-propanediammonium hydroiodate is replaced with N,N-2-ethylcyclohexane-1,4-diammonium hydrochloride. Compared with the perovskite film without diammonium ions, N,N-2-ethylcyclohexane-1,4-diammonium hydrochloride contains cyclohexane similar to benzene rings, which are regularly distributed on the surface to form a two-dimensional layer, thus improving the stability of the perovskite.

[0062] Example 6

[0063] The other steps are the same as in Example 1, except that 2,2-dimethyl-1,3-propanediammonium hydroiodate is replaced with N,N,N',N'-tetramethyl-terephthalic acid diammonium hydrochloride. Compared with the perovskite film without diammonium ions, the perovskite doped with N,N,N',N'-tetramethyl-terephthalic acid diammonium hydrochloride contains a benzene ring macromolecule, which is beneficial to improve the hydrophobicity of the perovskite and thus improve its stability.

[0064] Example 7

[0065] The other steps are the same as in Example 1, except that 2,2-dimethyl-1,3-propanediammonium hydroiodate is replaced with N,N-diphenylethylenediammonium hydrochloride. Compared with the perovskite film without diammonium ions, the perovskite doped with N,N-diphenylethylenediammonium hydrochloride contains two large benzene ring molecules. The macromolecules are distributed on the grain boundaries of the perovskite surface, passivating the defects in the grain boundaries, reducing the defects in the perovskite, and improving the efficiency of the perovskite. The hydrophobicity of the organic macromolecules improves the stability of the perovskite.

[0066] Example 8

[0067] The other steps are the same as in Example 1, except that 2,2-dimethyl-1,3-propanediammonium hydroiodate is replaced with 1,4-phenyldimethyldiiodide. Compared with the perovskite film without diammonium ions, the rigid structure of 1,4-phenyldimethyldiiodide is more likely to form a two-dimensional perovskite layer due to its regular distribution on the perovskite surface, which improves the hydrophobicity of the perovskite surface and thus improves the stability of the perovskite.

[0068] The performance of the obtained solar cell is close to that of Example 1.

[0069] This invention is not limited to the embodiments described above and can be varied within the scope of the claims. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claims. The scope of protection of this invention is defined by the appended claims and their equivalents.

[0070] Matters not covered in this invention are common knowledge.

Claims

1. A high-efficiency and stable perovskite solar cell based on diammonium ion doping, characterized in that, The solar cell consists of, from bottom to top, ITO conductive glass, an electron transport layer, a perovskite absorber layer doped with diammonium halide, a hole transport layer, and a gold electrode. The chemical formula of the perovskite layer is Rb 0.02-0.05 (FA 0.75-0.95 Cs 0.05-0.25 ) 0.98-0.95 PbI 2.91 Br 0.03 Cl 0.06 Thickness is 300-500 nm; The doping amount of diammonium halide in the perovskite absorber layer is 0.1-2 mol% of the molar mass of lead iodide in the perovskite; The diammonium halide salts specifically mentioned are 2,2-dimethyl-1,3-propanediammonium hydroiodate, 1,4-phenylenediammonium hydroiodate, N,N-2-ethylcyclohexane-1,4-diammonium hydrochloride, N,N-2-methyl-1,4-butanediammonium hydrochloride, N,N-dimethyl-p-diammonium hydrochloride, N,N-dimethyl(4-piperidinyl)methylammonium diammonium hydrochloride, (S)-3-(1-aminoethyl)-N,N-dimethylphenylenediammonium hydrochloride, (R)-N,N-diethylpyrrolidine-3-diammonium hydrochloride, and N,N-dimethyl... N,N,N',N'-tetramethyl-1,2-diammonium hydrochloride, N,N,N'-triethylethylenediammonium hydrochloride, N,N-diphenylethylenediammonium hydrochloride, 2,2'-(ethylenedioxy)bis(ethylenediammonium)hydroiodide, VUF8430 diammonium hydrobromide, 1,4-phenyldimethyldibromide, 1,4-phenyldimethyldiiodide, N1-(tert-butyl)ethane-1,2-diammonium hydrochloride, or N1-isopropyl-N2,N2-dimethylethane-1,2-diammonium hydrochloride; The hole transport layer is made of Spiro-OMeTAD material and has a thickness of 200-500 nm. The electron transport layer is made of SnO2 and has a thickness of 10-30 nm. The thickness of the ITO conductive glass substrate is 300-600 nm; The thickness of the gold electrode is 60-200 nm; The method for fabricating a high-efficiency and stable perovskite solar cell based on diammonium ion doping includes the following steps: (1) Fabrication of the electron transport layer: A tin dioxide solution with a volume ratio of SnO2:water = 1:1-8 was spin-coated onto ozone-treated ITO conductive glass at a rotation speed of 2000-6000 rpm / min to form an electron transport layer of 10-30 nm. The glass was then annealed at 100-180℃ for 20-50 minutes to obtain the electron transport layer. (2) Preparation of perovskite light-absorbing layer: On the electron transport layer, after spin-coating the perovskite precursor solution, a perovskite absorber layer doped with diammonium halide with a thickness of 300-500 nm is obtained by vacuum flash evaporation. The perovskite precursor solution contains 0.1-20 mg / mL diammonium halide, 1.1-1.6 mmol / mL FAI, 0.07-0.37 mmol / mL CsI, 0.025-0.05 mmol / mL RbI, 0.01-0.8 mmol / mL MACl, 0.01-0.1 mmol / mL PbCl2, 1.48-1.70 mmol / mL PbI2, and 0.01-0.15 mmol / mL PbBr2; the solvents are NMP and DMF, with a volume ratio of NMP:DMF = 1:4-9. The spin coating speed is 2000-6000 rpm / min, the time is 3-20 s, the annealing temperature is 100-150 ℃, the time is controlled at 3-50 min, and the device structure is ITO / SnO2 / diammonium halide-doped perovskite. (3) Preparation of hole transport layer: Spiro-OMeTAD hole transport layer solution was spin-coated onto the surface of the perovskite light absorption layer at a spin speed of 3000-4500 rpm and a thickness of 200-500 nm to obtain the hole transport layer. (4) Fabrication of gold electrodes: The device obtained in step (3) is placed in a thermal evaporator, and the vacuum level reaches 10. -4 -10 -6 After Pa, Au electrodes with a thickness of 60-200 nm are deposited at an evaporation rate of 0.1-0.9 nm / s, ultimately obtaining a high-efficiency and stable perovskite solar cell based on diammonium ion doping.

2. The high-efficiency and stable perovskite solar cell based on diammonium ion doping as described in claim 1, characterized in that, In the preparation method, the Spiro-OMeTAD hole transport layer solution provided in step (3) is prepared as follows: 50-150 mg of Spiro-OMeTAD powder is added to a container, then 10-40 μL of 4-tert-butylpyridine and 10-50 μL of acetonitrile containing lithium bis(trifluoromethanesulfonyl)imide are added, and finally 1-5 mL of chlorobenzene is added to obtain the hole transport layer precursor solution. The concentration of the acetonitrile solution of lithium bis(trifluoromethanesulfonyl)ammonium is 400~600 mg / mL.

Citation Information

Patent Citations

  • Wide-band-gap perovskite thin film, solar cell and preparation method of wide-band-gap perovskite thin film

    CN114709340A